2019
DOI: 10.3390/ma12091381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multi-Directional Forging on the Microstructure and Mechanical Properties of β-Solidifying TiAl Alloy

Abstract: This study systematically investigated the influence of multi-directional forging (MDF) on the microstructural evolution, hot deformation behavior, and tensile properties of a β-solidifying TiAl alloy. The initial lamellar microstructure of an as-cast alloy was remarkably refined and homogenized by three-step MDF. High temperatures and multi-pass deformations were conducive to the decomposition of lamellae. A crack-free billet was obtained through three-step MDF, with a deformation temperature of 1250 °C and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thermal deformation is a suitable way to obtain a fine-grained microstructure, which is beneficial for the ductility of TiAl alloys [5,8]. Past research has confirmed that the hot workability of TiAl alloys can be significantly enhanced by the β phase with a disordered body-center cubic lattice at above 1150 °C [9,10]. The content of the β phase depends closely on β-stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal deformation is a suitable way to obtain a fine-grained microstructure, which is beneficial for the ductility of TiAl alloys [5,8]. Past research has confirmed that the hot workability of TiAl alloys can be significantly enhanced by the β phase with a disordered body-center cubic lattice at above 1150 °C [9,10]. The content of the β phase depends closely on β-stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the ductile–brittle transition temperature (DBTT) of the current alloy should be 750–800 °C. According to previous studies, the DBTT of TiAl alloys without Nb is just 700–750 °C [20]. By contrast, the DBTT of high-Nb containing TiAl alloys can reach to more than 800 °C due to the high Nb content [46].…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of the as-forged billet was analyzed by electron back-scattered diffraction (EBSD, FEI, Hillsboro, OR, USA). Samples for TEM and EBSD were prepared using a standard procedure, which has been described in previous research [20].…”
Section: Methodsmentioning
confidence: 99%